2016
DOI: 10.1007/s12031-016-0748-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MicroRNA-221 Alleviates Neuropathic Pain Through Targeting Suppressor of Cytokine Signaling 1

Abstract: Neuropathic pain results in considerable trouble to people's physical and mental health. The pathophysiological mechanisms underlying its occurrence and development remain unclear. A large number of experiments show that microRNAs (miRNAs) play a major role in the pathogenesis of neuropathic pain and neuroinflammation resulting from nerve injury. Among various miRNAs, microRNA-221 (miR-221) overexpression has been reported in a chronic constrictive injury (CCI)-induced rat model of neuropathic pain. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…miR‐146a is considered an important part of feedback mechanisms in response to inflammatory stimuli, modulating inflammatory responses through IRAK‐1 and other targets . Recently, the role of miR‐221 in inflammation, through targeting of SOCS1 and modulation of the NF‐kB and p38 MAPK signalling pathways, has been suggested . In our study, miR‐146a and miR‐221 expression correlated with IL‐1b in newborns from normal weight mothers (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…miR‐146a is considered an important part of feedback mechanisms in response to inflammatory stimuli, modulating inflammatory responses through IRAK‐1 and other targets . Recently, the role of miR‐221 in inflammation, through targeting of SOCS1 and modulation of the NF‐kB and p38 MAPK signalling pathways, has been suggested . In our study, miR‐146a and miR‐221 expression correlated with IL‐1b in newborns from normal weight mothers (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…40 Inhibition of MicroRNA-221 alleviates neuropathic pain through targeting suppressor of cytokine signaling 1. 41 By regulating suppressor of cytokine signaling 3, Downregulation of microRNA-218 can relieve neuropathic pain. 32 These studies have indicated that targeting specific miRNAs can reduce neuropathic pain development.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shi et al (39) reported that miR-195 induced by SNL aggravated neuropathic pain by inhibiting Atg14. Suppression of miR-155, miR-19a or miR-221 inhibited neuropathic pain through targeting suppressor of cytokine signaling 1 (11,40,41). Intrathecal injection of miR-96 and miR-183 alleviated neuropathic pain by downregulation of sodium channel Nav1.3 expression (42,43).…”
Section: Discussionmentioning
confidence: 99%